Assessment of Artificial Intelligence and Film-Based Media integration in Innovative Language teaching among Secondary School Teachers in Okitipupa Metropolis (Federal University Gusau Faculty of Education Journal, 2026)
This study investigated teachers’ perceptions of integrating artificial intelligence (AI) tools and film-based media to enhance learner engagement, motivation, and linguistic competence in English and Yorùbá classrooms in Okitipupa metropolis. Using a cross-sectional survey design, a stratified purposive sample of 50 practising senior secondary school teachers representing public and private schools and language specialisations was selected. Data were collected through a validated structured Likert-scale questionnaire, with a reliability coefficient of 0.72. Descriptive statistics, including frequencies, percentages, means, medians, and standard deviations, were used to summarise responses. Findings indicated that English teachers reported higher frequency of using AI and films, while Yorùbá teachers exhibited greater confidence in their integration. Both groups perceived positive effects on learner engagement, motivation, and linguistic competence, with Yorùbá teachers highlighting focus and interaction and English teachers emphasising contextual language understanding. The study concluded that perceived competence did not always align with actual usage and recommended professional development, resource access, and sharing of best practices to support effective classroom integration.